A phase II study of carboplatin AUC-10 guided by positron emission tomography–defined metabolic response in metastatic seminoma. (July 2019) - Shamash, Jonathan; Syed, Rizwan; Sarker, Shah-Jalal; Sarwar, Naveed; Sharma, Anand; Mutsvangwa, Katherine; Coetzee, Carike; Wilson, Peter; Rustin, Gordon J.
Abstract: Introduction: Carboplatin monotherapy for metastatic seminoma at a dose of AUC-10 has shown promising activity. Three or four cycles have been given with most haematological side-effects seen with the 4th cycle. An early response might allow de-escalation of therapy. Methods: Forty-eight patients with metastatic seminoma (International Germ Cell Cancer Collaborative Group good prognosis) were recruited. Positron emission tomography (PET) scanning was performed before and after one cycle of carboplatin. Those with a Deauville score of 3 or less were given a total of three cycles of carboplatin, the rest received four. Results: PET scanning allowed 44% to receive three cycles of carboplatin. With a median follow-up of 31.2 months, 95.6% (95% confidence interval: 83.5%–98.9%) were progression free. The overall survival at 2-years was 100%. Lower stage (2A and 2B) disease was significantly ( P = 0.001) associated with the better metabolic response, but the association was not strong (correlation coefficient = −0.48). Over a third of the blood products given were used to support the 4th cycle. The regimen was well tolerated with a low incidence of grade III neutropenic sepsis or nausea and vomiting (<3% cycles). Conclusion: Carboplatin AUC-10 monotherapy is effective with low toxicity. Early changes during PET scanning may allow de-escalation of therapy in high volume disease—comparison against combination therapy is warranted. Clinicaltrials.gov identifier: NCT02272816 . EudraCT number: 2009-009882-33. Highlights: Carboplatin monotherapy at AUC-10 is an effective therapy for metastatic seminoma. Positron emission tomography–computerised tomography after one cycle allows a reduction of therapy without compromising efficacy. Non-haematological toxicity is mild. Salvage of relapse with combination cisplatin-based therapy is possible.